Cross-sectional return predictability: the predictive power of return asymmetry, skewness and tail risk - Xu, Zhongxiang (2017)
This thesis attempts to investigate the cross-sectional predictive power of return asymmetry, skewness and tail risk. It mainly consists of three empirical chapters on the relation between predictive patterns of the return distribution and expected stock returns.